Pemilihan Calon Manager Dari Pegawai Berprestasi Menggunakan Metode Profile Matching Pada CV. Glofacia Oceanic - Parulian Sinaga, Dedi Candro; Sianipar, Baringin; Marpaung, Preddy (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
At this time, the company CV. Glofacia Oceanic in Medan City is looking for employees to be appointed as Managers and for the Selection of Candidates for Managers who have difficulties in selecting employees who have good work performance within the company, then based on work goals and attendance, which are evaluation materials for employee appraisals to become managers. For employees who are elected will be managers in the CV. Glofacia Oceanic. The number of employees becomes the owner of difficulties for company owners in selecting employees who are appointed to become managers, so it cannot be denied that in the selection of outstanding employees at CV. Oceanic Glofacia is often done not objectively. To find out which internal employees of the company are performing well, it is necessary to assess the performance of the employees. At the time of an assessment in choosing a prospective manager, including using a decision support system to help solve a problem. The method that will be used to select prospective internal managers is the Profile Matching method with the application of this method in selecting prospective managers, so there are no errors in decision making. So it is hoped that the Profile Matching Method can provide value objectively to employees and assist the company's director in providing employee performance appraisals.